RETRACTED: The efficacy and adverse effects of anlotinib in the treatment of high-grade glioma: A retrospective analysis - Shen, Fangcheng; Li, Jing; Liu, Feng; Sun, Ni; Qiu, XiangNan; Ding, Wei; Sun, XiangDong (Frontiers in Oncology, 2023)
Anlotinib, a novel multi-kinase inhibitor, was found to improve the PFS in brain metastases. This paper retrospectively analyzed 26 newly diagnosed or recurrent high-grade gliomas from 2017-2022, and the patients received oral anlotinib during both concurrent postoperative chemoradiotherapy, or after recurrence. Efficacy was evaluated according to the RANO criteria, and the main study endpoints were PFS at 6 months and OS at 1 year. After the follow-up until May 2022,13 patients survived and 13 patients died, with a median follow-up time of 25.6 months. The DCR rate was 96.2% (25/26), and the ORR rate was 73.1% (19/26). The median PFS after oral anlotinib was 8.9 months (0.8-15.1), and the PFS at 6 months was 72.5%. The median OS after oral anlotinib was 12 months (1.6-24.4), and the OS at 12 months was 42.6%. Anlotinib-related toxicities were observed in 11 patients, mostly grade 1-2. In the multivariate analysis, patients with KPS above 80 had a higher median PFS of 9.9 months (P=0.02), and their sex, age, IDH mutation, MGMT methylation, and whether anlotinib was combined with chemoradiotherapy or maintenance treatment, and had no effect on PFS.